Work Stress at Nurses in Dahlia II Ngudi Waluyo Public Hospital Blitar - Ulfa Husnul Fata (University of Muhammadiyah Malang, 2016)
Work stress is the distress ecperienced by nurses in the face of work. Job stress ecperienced by nurses if not addressed it will impact on the poor performance and quality of services provided. The purpose of the study was to provide an oveview of nurses work stress in Dahlia II Ngudi Waluyo Hospital Blitar. The method of this study was descriptive with respondents are all nurses at Dahlia II Ngudi Waluyo Blitar with sample size of 22 respondents. The data collection used questionnaires. The result of this study showed that64% of female respondents experienced work stress moderate category, 32,5% of respondents who experienced stress ages were in the range of age 36 – 45 years old, 73% of respondents with level of education was Diploma of Nursing experienced moderate stress, 46% of respondents with working period of 2 – 10 years experience moderate stress, and 59% of respondents who experienced moderate stress category of being a merried respondents. The importants to identifying the work stress at the nurses in the inpatient unit in order to determine the level of work stress experienced and immediately seek solutions to reduce the stress level of nureses in the patient unit. Therefore, management of the stress training was considered important to reduce the stress of nurses in the inpatient unit.